Accruals in the prediction of forthcoming cash flows in the companies listed at Pakistan Stock Exchange - Rai, I. H.; Noor Saadah,; Faridah, I.; Jaspal, S. J. S. * (Econjournals, 2020)
This research founds the relative predictabilities of accruals and further disaggregated accruals– trading accruals, non-trading accruals, and financial accruals in the estimation of future cash flows. The research also examines the effect of the global financial crisis on this association between accruals and future cash flow prediction. The research uses annual data from the period of 1999 to 2018 from 453 firms, which includes 9060 observations. The whole sample period covers data from 1999 to 2018, during the financial crisis period from 2008-2009 and Pre financial crisis period from 1999 to 2007 and Post global financial crisis period 2010 to 2018. To examine the relationship between accruals, disaggregated accruals, and estimation of future cash flows, hypotheses were developed and seasoned through OLS. The outcomes confirm that financial accruals, non-trading accruals, and total aggregated accruals were significant, but trading accruals was not a significant contributor to the estimation of future cash flows. Moreover, there was no significant effect of the global financial crisis on the relationship among disaggregated accruals and forecast of imminent cash flows during Pre and Post and during the global financial crisis period.